Understanding the significance of patient safety and designing a novel curriculum using Kern's six-step approach - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
The branch of medicine and provision of clinical care is quite complex and challenging owing to the involvement of a number of stakeholders and parameters. The available global estimates suggest that the incidence of adverse events is one the rise and it has been identified as one among the 10 most frequent reasons for death and disability worldwide. Considering that significant developments have been made in modern medicine, it is quite unacceptable. The ideal and cost-effective approach that is expected to make it as a long-term behavior among the future generation of doctors, is by exposing the undergraduate medical students to patient safety curriculum during their training period. At present, the need of the hour is to design a comprehensive patient safety curriculum and as it is a novel topic, we can adopt Kern's six-step approach for the same. In conclusion, patient safety is an integral aspect of clinical medicine and being a health care professional, it is our primary responsibility to not only deliver quality assured care but also take care of patient safety. Thus, it is high time that steps are taken at the medical college level to design a formal patient safety curriculum and then implement the same in collaboration with the Curriculum Committee and the Medical Education Unit.